The carbon efficient city - Hurd, A-P (University of Washington Press, 2012)
"The Carbon Efficient City shows how regional economies can be aligned with practices that drive carbon efficiency. It details ten strategies for reducing carbon emissions in our cities: standardized measurement, frameworks that support innovation, regulatory alignment, reducing consumption, reuse and restoration, focus on neighborhoods, providing spaces for nature, use of on-site life cycles for water and energy, coordination of regional transportation, and emphasis on solutions that delight people. Although climate change is recognized as an urgent concern, local and national governments, nonprofits, and private interests often work at cross purposes in attempting to address it. The Carbon Efficient City's focus on concrete, achievable measures that can be implemented in a market economy gives it broad appeal to professionals and engaged citizens across the political spectrum."--Publisher